Propulsion strategy in the gait of primary school children; the effect of age and speed. - Lye, J.; Parkinson, Stephanie; Diamond, N.; Downs, Jennepher; Morris, Susan (Elsevier BV; North Holland, 2016)
The strategy used to generate power for forward propulsion in walking and running has recently been highlighted as a marker of gait maturation and elastic energy recycling. This study investigated ankle and hip power generation as a propulsion strategy (PS) during the late stance/early swing phases of walking and running in typically developing (TD) children (15: six to nine years; 17: nine to 13years) using three-dimensional gait analysis. Peak ankle power generation at push-off (peakA2), peak hip power generation in early swing (peakH3) and propulsion strategy (PS) [peakA2/(peakA2+peakH3)] were calculated to provide the relative contribution of ankle power to total propulsion. Mean PS values decreased as speed increased for comfortable walking (p<0.001), fast walking (p<0.001) and fast running (p<0.001), and less consistently during jogging (p=0.054). PS varied with age (p<0.001) only during fast walking. At any speed of fast walking, older children generated more peakA2 (p=0.001) and less peakH3 (p=0.001) than younger children. While the kinetics of running propulsion appear to be developed by age six years, the skills of fast walking appeared to require additional neuromuscular maturity. These findings support the concept that running is a skill that matures early for TD children.